An eco-friendly wood adhesive from soy protein and lignin: performance properties. Issue 122 (24th November 2015) - Luo, Jing; Luo, Jianlin; Yuan, Cheng; Zhang, Wei; Li, Jianzhang; Gao, Qiang; Chen, Hui
Abstract : The aim of this study was to improve the water resistance of a soybean meal-based adhesive with a low-cost lignin-based resin (LR). Abstract : The aim of this study was to improve the water resistance of a soybean meal-based adhesive with a low-cost lignin-based resin (LR). The LR could react with active groups on the protein molecules and itself to form a cross-linking and interpenetrating network, which improved the water resistance of the resultant adhesive. In addition, adding LR increased the thermal stability of the cured adhesive, forming a cross-linked protein molecule-based structure, and created a smooth surface with fewer holes and cracks to prevent moisture intrusion, which further improved the water resistance of the resultant adhesive. Using LR also resulted in an appropriate viscosity which benefited adhesive distribution during the plywood hot press process and formed a stronger interlock with wood, thus creating good wet shear strength of the resultant plywood. Incorporating 10 wt% LR effectively improved the wet shear strength of the resultant plywood by 200% to 1.05 MPa, which met interior-use plywood bond strength requirement. The resultant adhesive had a solid content of 32.65% and viscosity of 499 400 mPa s, which were acceptable for industrial application in plywood fabrication.